A vivência de práticas de oralidade e escrita pela criança - Bassani, Sabrina Caroline (2018)
In this work, entitled "The experience of oral and written practices by the child", it is sought to understand the experience of the social practices of language involving orality and writing by the child of the initial years of elementary school. The general objective is to describe the experience of the social practices of oral and written languages by the child of the 2nd year of elementary school, based on the analysis of their discursive manifestation. This work is justified by the purpose of collaborating with the study of the relations between speech and writing and, above all, to evidence learners as subjects that establish relationships between the modalities of language and rely on the language experiences they already have to appropriate themselves of the writing system. The theoretical foundations of this research follow the principles and presuppositions of the dialogical approach of Mikhail Bakhtin and his Circle (1992, 2004), in which the subject is considered as a social being who appropriates the word through experience with the world that surrounds him or her. Such assumptions dialogue with studies of the Analisys of Conversation from the German researchers Peter Koch and Wulf Osterreicher, whose works came to Brazil through Marcuschi (2008, 2010) regarding the conception of language and the typological continuum between orality and writing. Regarding the methodology, it is a descriptive, explanatory, bibliographic and qualitative research, with action research carried out at the Municipal School of Basic Education Barra Funda, RS. The corpus of the research comprises a set of textual, oral and written productions of students of the 2nd year of elementary school. The study demonstrates that the child experiences social practices of oral and written languages and that such practices are responsible for the hybridization of their textual productions. These, in turn, occupy a specific space in the typological continuum between orality and writing that comes much closer to orality because the children's language experiences are essentially oral.